2015
DOI: 10.3987/com-14-s(k)1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,6-Diaminoazulenes by the SNAr Reaction with Cyclic Amines

Abstract: 2-Amino-6-bromoazulene derivatives reacted with cyclic amines (pyrrolidine, piperidine and morpholine) under the sealed-tube conditions to afford the corresponding 2,6-diaminoazulenes in excellent yields. Aromatic compounds with multiple-amino functional groups have been of great interest owing to their potential applications in organic electronic devices, such as hole transport materials for organic light-emitting diodes. 1 Therefore, a large number of synthetic procedures for aromatic compounds with multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…Thus, the reaction was performed at 150 °C in a sealed tube, as these had been shown previously to be successful conditions for the synthesis of 2,6diaminoazulene derivatives. 13 The S N Ar reaction of 2 with morpholine at 150 °C in a sealed tube afforded the desired product 10…”
Section: Nhmentioning
confidence: 99%
“…Thus, the reaction was performed at 150 °C in a sealed tube, as these had been shown previously to be successful conditions for the synthesis of 2,6diaminoazulene derivatives. 13 The S N Ar reaction of 2 with morpholine at 150 °C in a sealed tube afforded the desired product 10…”
Section: Nhmentioning
confidence: 99%
“…[19] Recently, we have developed various redoxactive chromophores for the creation of stabilized electro-7 chromic materials. [20] As a part of the study, we have reported several TCBD derivatives bearing azulenyl, [10][11][12]14] ferrocenyl, [21] and 2-oxo-2H-cyclohepta[b]-3-furyl [22] substituents, and we have identified some hybrid structures of violene and cyanine with redox activities. [23] Similarly to the TCBD derivatives described previously, these new 1-AzTCBD compounds connected through a 1,3,5-tri(1-azulenyl)benzene core should exhibit a reversible color change under electrochemical reaction conditions, because these compounds showed highly reversible redox waves by CV.…”
Section: Electrochemistrymentioning
confidence: 99%
“…Recently, we reported the redox potentials of a series of TCBD derivatives. [10][11][12]14] The study revealed that the first reduction potentials of the 1-AzTCBD compounds substituted by π-electron cores decreased as the number of substituted TCBD units increased. With respect to the number of stages for the reduction, Diederich et al reported that the compound with three DAA-substituted TCBD units connected by a 1,3,5-benzenetriyl spacer shows a six-stage reversible reduction wave within a narrow potential range.…”
Section: Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Sowohl das 4-als auch das 6-Fluor-Azulen setzten sich mit Morpholin glatt um und ergaben 3a bzw. Da in unserem Fall alle Positionen des fünfgliedrigen Rings blockiert sind, wird eine selektive Funktionalisierung des siebengliedrigen Rings mçglich.…”
unclassified